2011
DOI: 10.1111/j.1742-7843.2011.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Piroxicam Reverses Endotoxin‐Induced Hypotension in Rats: Contribution of Vasoactive Eicosanoids and Nitric Oxide

Abstract: Nitric oxide (NO) produced by inducible NO synthase (iNOS) is responsible for endotoxin-induced vascular hyporeactivity and hypotension resulting in multiple organ failure. Endotoxic shock is also characterized by decreased expression of constitutive cyclooxygenase (COX-1), cytochrome P450 (CYP) 4A and endothelial NOS (eNOS). Our previous studies demonstrated that dual inhibition of iNOS and COX with a selective COX-2 inhibitor, NS-398, or a non-selective COX inhibitor, indomethacin, restores blood pressure pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Our previous studies suggested that the endotoxemia-induced increase in NO production primarily via iNOS suppresses renal CYP4A expression and activity, and selective inhibition of iNOS with 1,3-PBIT restores renal CYP4A protein and activity and MAP presumably due to increased production of AA metabolites derived from CYP4A [49,51]. The results of the present study together with our previous findings using 5,14-HEDGE and COX inhibitors [31,33,50,52] demonstrate that LPS causes a decrease in CYP4A1 mRNA and protein expression not only in the kidney, but also in the heart, thoracic aorta, and superior mesenteric artery, together with reduced systemic and tissue levels of 20-HETE. In contrast to our findings, Anwar-Mohamed et al [26] demonstrated that CYP4A1 mRNA expression was increased in the heart of inflamed animals at 6, 12, and 24 h by 400%, 900%, and 6000%, respectively, after injection of LPS ( E. coli LPS, O127:B8, 1 mg/kg, i.p.)…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our previous studies suggested that the endotoxemia-induced increase in NO production primarily via iNOS suppresses renal CYP4A expression and activity, and selective inhibition of iNOS with 1,3-PBIT restores renal CYP4A protein and activity and MAP presumably due to increased production of AA metabolites derived from CYP4A [49,51]. The results of the present study together with our previous findings using 5,14-HEDGE and COX inhibitors [31,33,50,52] demonstrate that LPS causes a decrease in CYP4A1 mRNA and protein expression not only in the kidney, but also in the heart, thoracic aorta, and superior mesenteric artery, together with reduced systemic and tissue levels of 20-HETE. In contrast to our findings, Anwar-Mohamed et al [26] demonstrated that CYP4A1 mRNA expression was increased in the heart of inflamed animals at 6, 12, and 24 h by 400%, 900%, and 6000%, respectively, after injection of LPS ( E. coli LPS, O127:B8, 1 mg/kg, i.p.)…”
Section: Discussionsupporting
confidence: 80%
“…We have previously demonstrated that selective inhibition of iNOS with phenylene-1,3-bis(ethane-2-isothiourea) dihydrobromide (1,3-PBIT) prevents the fall in MAP, increase in HR, and vascular reactivity to norepinephrine as well as increased sGC and PKG activity associated with systemic and/or aortic NO and nitrotyrosine production 4 h after LPS administration to rats [36,4749]. Recently, we have reported that an increase in iNOS protein expression is associated with a decrease in eNOS and COX-1 protein expression in the renal, cardiac, and vascular tissues as well as vascular hyporeactivity to norepinephrine in thoracic aorta and superior mesenteric artery 4 h after LPS administration to rats [31,32,50]. These data suggested that overproduction of NO by iNOS associated with an increase in sGC and PKG activity in vascular tissue contributes to the hypotension and vascular hyporeactivity to norepinephrine 4 h after LPS injection to rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPS produced a fall in MAP and increase in HR within 1 h that was sustained for 4 h. Administration of 5,14-HEDGE prevented the LPS-induced fall in blood pressure and increase in HR within 1 h. Compensatory mechanisms, including activation of the renin-angiotensin-aldosteron system, increased sensitivity of baroreceptor reflex mechanisms, and increased production of endothelin-1 and catecholamines, which are known to activate phospholipase A 2 and release AA from tissue lipids, and results in prostaglandin synthesis, and also stimulate production of reactive nitrogen and oxygen species, have also been reported to be responsible for the changes in the formation of vasoregulatory molecules that could contribute to the fall in blood pressure during LPS-induced endotoxemia [1]. Our previous studies suggested that systemic administration of LPS to rats causes a decrease in CYP4A1 mRNA and protein expression in the kidney, heart, thoracic aorta, and superior mesenteric artery associated with reduced systemic and tissue levels of 20-HETE [40–42,45,46]. In contrast to our findings, Anwar-Mohamed et al [20] demonstrated that CYP4A1 mRNA expression was increased in the heart of inflamed animals at 6, 12, and 24 h by 400%, 900%, and 6000%, respectively, after injection of LPS ( E. coli LPS, O127:B8, 1 mg/kg, i.p.)…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies with the use of the nonselective COX inhibitor, indomethacin, suggest that inhibition of renal iNOS protein expression as well as systemic nitrite and PGE 2 levels by indomethacin restores MAP presumably due to increased production of 20-HETE derived from CYP4A in endotoxemic rats [40]. Our recent studies also suggest that a decrease in the expression and activity of COX-2 and iNOS associated with an increase in CYP4A1 expression and 20-HETE synthesis contributes to the effect of piroxicam, a preferential COX-1 inhibitor, helping to prevent the hypotension during rat endotoxemia [45]. More recently, we have demonstrated that inhibition of PGI 2 and PGE 2 synthesis and NO production by a selective COX-2 inhibitor, N-(2-cyclohexyloxy-4-nitrophenyl)-methansulphonamide (NS-398), restores blood pressure due to increased systemic and renal levels of 20-HETE [44].…”
Section: Introductionmentioning
confidence: 99%